BOUNDING SURFACE COUPLED FINITE ELEMENT CONSOLIDATION ANALYSIS OF NORMALLY AND OVERCONSOLIDATED CLAYS (Journal of Engineering, 2024)
The radial mapping version of the bounding surface plasticity model is implemented in a computer program to predict the response of cohesive soils. The eight-noded isoparametric element and Biot’s theory are used in this study for analyzing soil consolidation problems. The model has been used in the analysis for two classes of problems. The first involves the comparison of model predictions with the results of laboratory tests in compression and extension for normally and overconsolidated clays. The second class involves using the model to predict the results of one- and two-dimensional finite element problems of soil consolidation. The comparisons with experiments demonstrate that the model, through its simplicity, can describe realistically the soil response under different monotonic loading conditions at any overconsolidation ratio. The comparison between the bounding surface plasticity model with the classical modified Cam clay model shows considerably different rates and magnitudes of settlement, and different pore pressure behavior during the consolidation process.